Perceptions of social, emotional, and functional values in patients with type 2 diabetes mellitus and their satisfaction with primary health care services - Budrevičiūtė, Aida (Prim Health Care Res Dev, 2019)
AIM: To explore the relationships between social, emotional, and functional values, and satisfaction of patients with type 2 diabetes mellitus (T2DM) with an emphasis on Lithuanian primary health care services providers. BACKGROUND: Academics and practitioners are encouraging more research on service value conceptually and empirically. Primary health care settings (PHCS) use modern management of value creation for patients with chronic diseases to increase the satisfaction of patients. Satisfaction of patients is the most important factor of competitive advantage for the PHCS. In this study, perceived value concept is dealt with in a multidimensional way. The fact that the perceived value in health sector has not previously been examined as multidimentionally has increased the importance of this research. METHODS: The study strategy is based on focus group discussions of executives and survey of patients with T2DM in the primary health care sector. The target of focus group discussions is to gain knowledge about factors developing the competitive advantage of PHCS. The survey of patients with T2DM is the background to test the conceptual model of perceived value importance on satisfaction. The study uses coefficients of correlation, exploratory factor analysis, and linear regression. FINDINGS: The results of focus groups revealed the factors of competitive advantage related to perspectives of health policy, organization, human resources, and patients. The results of the survey established statistically significant links between social value and satisfaction, and functional value and satisfaction. Emotional value decreased satisfaction of patients with T2DM.